1997
DOI: 10.1046/j.1469-8137.1997.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Root production and turnover and carbon budgets of two contrasting grasslands under ambient and elevated atmospheric carbon dioxide concentrations

Abstract: Sl'MMARYMonoliths of two contrasting vegetation types, a species-rich grassland on a brown earth soil over limestone and a species-poor community on a peat>' gley, were transferred to solardomes and grown under ambient (350 /d 1"') and elevated (600//I i"^) CO^ for 2 yr. Shoot biomass was unaltered but root biomass increased by 40-50% under elevated CO^. Root production was increased by elevated CO^ in the peat soil, measured both as instantaneous and cumulative rates, but only the latter measure was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…A few studies have observed changes in root demography under elevated CO # , and there seems to be a commonality among them. Elevated CO # increases fine-root production in most species, but this response can be dampened by low soil fertility (Pregitzer et al, 1995 ;Berntson & Bazzaz, 1996 ;Day et al, 1996 ;Tingey et al, 1996 ;Fitter et al, 1997 ;Kubiske et al, 1998 ;Pregitzer et al, 2000). Increases in fine-root production under elevated CO # undoubtedly give rise to a greater standing crop of fine roots, which has been documented in a large number of studies (Rogers et al, , 1997.…”
Section:  [  # ]        mentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies have observed changes in root demography under elevated CO # , and there seems to be a commonality among them. Elevated CO # increases fine-root production in most species, but this response can be dampened by low soil fertility (Pregitzer et al, 1995 ;Berntson & Bazzaz, 1996 ;Day et al, 1996 ;Tingey et al, 1996 ;Fitter et al, 1997 ;Kubiske et al, 1998 ;Pregitzer et al, 2000). Increases in fine-root production under elevated CO # undoubtedly give rise to a greater standing crop of fine roots, which has been documented in a large number of studies (Rogers et al, , 1997.…”
Section:  [  # ]        mentioning
confidence: 99%
“…In tree species, 40-50% of fine roots die and disappear within a single year (Hendrick & Pregitzer, 1992 ;Burke & Raynal, 1994 ;Fahey & Hughes, 1994), and this proportion can be even greater in grasslands (Fitter et al, 1997). Moreover, elevated CO # can disproportionately increase net fine-root production over mortality (Pregitzer et al, 1995 ;Day et al, 1996 ;Pregitzer et al, 2000), although such a response is not universal (Berntson & Bazazz, 1996 ;Fitter et al, 1997). In contrast, above-ground litter production in most experiments occurs as a seasonal pulse deposited at the soil surface.…”
Section:  [  # ]        mentioning
confidence: 99%
See 2 more Smart Citations
“…Grassland systems, on the other hand, can be studied as intact ecosystems in manipulative experiments (e.g. Fitter et al, 1997), and the arbitrary separation of responses by fine roots and coarse roots is unnecessary. In an annual crop system, the important research questions are more likely to revolve around root deployment and resource capture rather than equilibrium responses and C flux (Fitter et al, 1991).…”
Section:      mentioning
confidence: 99%